Microbial fuel cell-assisted utilization of glycerol for succinate production by mutant of Actinobacillus succinogenes - Zheng, Tianwen; Xu, Bin; Ji, Yaliang; Zhang, Wenming; Xin, Fengxue; Dong, Weiliang; Wei, Ping; Ma, Jiangfeng; Jiang, Min (Biotechnology for biofuels, 2021)
The global production of glycerol is increasing year by year since the demands of biodiesel is rising. It is benefit for high-yield succinate synthesis due to its high reducing property. A. succinogenes, a succinate-producing candidate, cannot grow on glycerol anaerobically, as it needs a terminal electron acceptor to maintain the balance of intracellular NADH and NAD . Microbial fuel cell (MFC) has been widely used to release extra intracellular electrons. However, A. succinogenes is a non-electroactive strain which need the support of electron shuttle in MFC, and pervious research showed that acid-tolerant A. succinogenes has higher content of unsaturated fatty acids, which may be beneficial for the transmembrane transport of lipophilic electron shuttle. MFC-assisted succinate production was evaluated using neutral red as an electron shuttle to recover the glycerol utilization. First, an acid-tolerant mutant JF1315 was selected by atmospheric and room temperature plasma (ARTP) mutagenesis aiming to improve transmembrane transport of neutral red (NR). Additionally, MFC was established to increase the ratio of oxidized NR to reduced NR. By combining these two strategies, ability of JF1315 for glycerol utilization was significantly enhanced, and 23.92 g/L succinate was accumulated with a yield of 0.88 g/g from around 30 g/L initial glycerol, along with an output voltage above 300 mV. A novel MFC-assisted system was established to improve glycerol utilization by A. succinogenes for succinate and electricity production, making this system as a platform for chemicals production and electrical supply simultaneously.